Pharmaceutical care for patients with coronary heart disease: transformation of pharmaceutical practice - N. A. Bilousova (Zaporozhye State Medical University, 2024)
The implementation of the National Recovery Plan of Ukraine in the field of "Health Care", namely the restoration of the pharmaceutical sector, improving the population's access to medicines and their proper use, taking into account the regulatory and legal field harmonized with European legislation, in the context of providing the qualified pharmaceutical care and pharmaceutical services requires application of modern approaches based on evidence-based medicine and implementation in pharmaceutical practice. Patients with cardiovascular diseases, who are provided with medication under the Reimbursement Program and prescriptions from doctors, must be accompanied by pharmaceutical care based on evidence-based medicine to ensure proper use of drugs and rational pharmacotherapy. The aim of the study was to investigate Ukrainian information and scientific databases, scientometric databases, i. e.: Embase, Web of Science, PubMed, and Cochrane Library to identify, generalize, and systematize scientific sources of medical and pharmaceutical data on providing patient-oriented pharmaceutical care to patients with coronary heart disease and predict the future vector of research on the specified topic. Results. The analysis of the main strategies of providing pharmaceutical care to patients with cardiovascular diseases, in particular, coronary heart disease in pharmaceutical practice was carried out; the most researched clusters of providing pharmaceutical care were identified; modern trends and tendencies in the provision of pharmaceutical care to patients with coronary heart disease were summarized. Conclusions. The development of providing qualified pharmaceutical care to patients with cardiovascular diseases is based on the principles of patient-oriented pharmacy and evidence-based medicine, which requires the design and implementation into the pharmaceutical practice of a sustainable conceptual model of providing patient-oriented pharmaceutical care by clinical pharmacists and pharmacists of pharmacy institutions with the expansion of the main roles, respectively the standards of Good Pharmacy Practice.